Determinants of Severe Metabolic Bone Disease in Very Low-Birth-Weight Infants with Severe Bronchopulmonary Dysplasia Admitted to a Tertiary Referral Center - Jensen, Erik A.; White, Ammie M.; Liu, Peihui; Yee, Keolamau; Waber, Brenda; Monk, Heather M.; Zhang, Huayan (American Journal of Perinatology, 2016)
Objective Nonrespiratory comorbidities are common among preterm infants with severe bronchopulmonary dysplasia (BPD) referred to tertiary perinatal centers. We evaluated the incidence, severity, and risk factors for metabolic bone disease (MBD) in this population.Study Design We conducted a retrospective cohort study of all infants born ≤ 1,500 g who were diagnosed with severe BPD in our single, tertiary referral center between September 2010 and October 2012. MBD severity was classified by serial radiography.Results Among the 83 infants diagnosed with severe BPD, 26 (31%) developed severe MBD (rickets). Male gender and lower gestational age and birth weight were associated with increased odds of severe MBD. After adjustment for these potential confounders, cytomegalovirus infection, postnatal growth restriction, surgical necrotizing enterocolitis, and blood culture confirmed sepsis were associated with increased odds of severe MBD. The cumulative duration of therapy with furosemide, hydrocortisone, and prednisolone each correlated with significantly greater probability of severe MBD.Conclusions Severe MBD was common in this referral-based cohort with severe BPD. The high incidence in this population is likely explained by the coexistence of multiple exposures and comorbidities associated with bone demineralization.
Keywords: metabolic bone disease; bronchopulmonary dysplasia; osteopenia; rickets; fracture